Analisis Peran Pemerintah Desa dalam Pengelolaan Dana Desa di Desa Bonto Tallasa Kecamatan Ulu Ere Kabupaten Bantaeng - Saharuddin Saharuddin (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2017)
This study aims to determine the role of Village Government in the Village Fund Management in the Bonto Tallasa village, Ulu Ere Sub-district of Bantaeng regency and the factors that influence it to achieve these objectives, used qualitative research methods using descriptive data. Data collection techniques used by means of observation, interviews, and documents and archives by using descriptive qualitative analysis techniques. The results showed: First, the role of Bonto Tallasa Village Government in the management of village funds run well in accordance with the prevailing laws and regulations, the Village Fund Management includes Planning, Implementation, and Accountability. The Planning Process undertaken by the Bonto Tallassa Village Government in accordance with the rules starting from the village meeting, the division of invitations, the village discussion and the determination of the RKP in the village. Then in terms of Implementation of village Fund management refers to the results of village planning until the establishment of RKP village and RPJM village, and the last is the Accountability Village Fund Management in Bonto Tallasa village has suitable with the existing legislation, but the process has not been able to run optimally, this is indicated by the level of accountability in the collection of accountability report, so that in the next stage of disbursement process too late. The two factors affecting the Village Fund Management include supporting and inhibiting factors. Supporting factors include community participation, facilities and infrastructure, while the inhibiting factor is community resources